Cross-cultural adaptation and validation of the Malay language version of the TZO-AZL Preschool Children Quality of Life questionnaire - Tay, C.G.; Jalaludin, M.Y.; Low, W.Y.; Lim, C.T. (SAGE Publications (UK and US), 2015)
The aim of this study is to evaluate the psychometric properties of the translated Malay language version of TZO-AZL Preschool Children Quality of Life (TAPQOL) questionnaire in preschool children. Preterm children and term children aged between two and five years were enrolled into the study. The Malay language version of TAPQOL and a set of questions regarding the child’s health status were answered by the caregivers. The internal consistency, Spearman’s correlation coefficients and principal component analysis (PCA) with Varimax rotation and Mann–Whitney U test for group comparison were employed to evaluate the psychometric properties of this instrument. A total of 258 children (120 preterm children and 138 term children) were recruited to this study with a response rate of 94%. All (sub)domains except one had Cronbach’s α coefficients of more than.7. The Spearman’s correlation coefficients between 12 subdomains were generally low. PCA supported the structural unidimensionality of the items in the instrument. Preterm children had lower quality of life scores than that of term children. Malay version of TAPQOL has multidimensional construct. It is a reliable and valid instrument for preschool children, with almost similar psychometric properties to the original version.